Dirichlet product and the multiple Dirichlet series over function fields - Hamahata, Yoshinori (Array, 2020)
We define the Dirichlet product for multiple arithmetic functions over function fields and consider the ring of the multiple Dirichlet series over function fields. We apply our results to absolutely convergent multiple Dirichlet series and obtain some zero-free regions for them.